2022
DOI: 10.31538/iijse.v5i2.2165
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Interest in Sharia Capital Market Investment of PTKIN And PTKIS Students

Abstract: Sharia investment is currently trending in the world of investment in Indonesia. Moreover, the current PTKI students are Generation Z, who are more familiar with the virtual world and the world of online investment. Thus, the understanding and interest of Generation Z in sharia investment needs to be analyzed in order to develop the Islamic capital market. The research article explains how high the understanding and interest of public and private Islamic university students towards Islamic capital market inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Jalari & Marimin (2020) found that the contribution of the academic community in the Islamic capital market is at most 30% of the total investors there are. The low investment of the academic community in the Islamic capital market is due to a need for knowledge and understanding on campuses where the academic community is an investor (Elmizan et al, 2022;Chen & Volpe, 1998). In addition, information systems are limited and less accessible, with limited professional and expert human resources in the field of the Islamic capital market.…”
Section: Introductionmentioning
confidence: 99%
“…Jalari & Marimin (2020) found that the contribution of the academic community in the Islamic capital market is at most 30% of the total investors there are. The low investment of the academic community in the Islamic capital market is due to a need for knowledge and understanding on campuses where the academic community is an investor (Elmizan et al, 2022;Chen & Volpe, 1998). In addition, information systems are limited and less accessible, with limited professional and expert human resources in the field of the Islamic capital market.…”
Section: Introductionmentioning
confidence: 99%
“…(Mustapha et al, 2017). The reason why investors start investing in the Islamic stock market is because the value of this stock has good resilience when the economy is in crisis and the capitalization of the Islamic capital market is still low compared to the conventional capital market (Elmizan et al, 2022). Today, the Islamic financial system has transformed as an important component of the global financial system with a valuation of more than $2 trillion per year.…”
Section: Introductionmentioning
confidence: 99%